2007
DOI: 10.1111/j.1746-6342.2006.03215.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the burden of hepatic encephalopathy

Abstract: Hepatic encephalopathy, a challenging complication of advanced liver disease, occurs in approximately 30-45% of patients with cirrhosis and 10-50% of patients with transjugular intrahepatic portosystemic shunt, while minimal hepatic encephalopathy affects approximately 20-60% of patients with liver disease.Although the total direct and indirect costs of hepatic encephalopathy have not been formally quantified, data from the Healthcare Cost and Utilization Project suggest that hepatic encephalopathy-related hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
201
0
6

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(224 citation statements)
references
References 18 publications
6
201
0
6
Order By: Relevance
“…Frequency of MHE increases as severity of liver dysfunction increases. 7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 91%
See 3 more Smart Citations
“…Frequency of MHE increases as severity of liver dysfunction increases. 7,10,12,[16][17][18] MHE predicts the development of overt HE and also adversely affects survival as shown by several studies. 7,10,18,[84][85][86][87] Das et al 10 studied the progression of MHE to overt HE in relation to severity of liver dysfunction and found that overt HE were more frequent in patients with MHE and Child-Turcotte-Pugh (CTP) score >6.…”
Section: Natural History and Survival In Minimal Hepatic Encephalopathymentioning
confidence: 91%
“…10 These patients pose a significant burden to their care givers depending on the severity of cognitive dysfunction. 2,12 Considering all these facts together, early detection and treatment of MHE is warranted and recommended. 2 This review focuses on MHE and its effect on daily functioning including driving skills, sleep disturbances and HRQOL in an individual.…”
Section: H Epatic Encephalopathy (He) Is a Neurocognitivementioning
confidence: 99%
See 2 more Smart Citations
“…Data in other countries are lacking, hence it causes a huge burden financially to the patient and society. 3 The West Haven Criteria are most often used to grade HE, with scores ranging from I-IV (IV being coma). However, it is a challenge to diagnose patients with minimal hepatic encephalopathy (MHE) or grade 1 HE; so it might be practical to combine these entities and name them covert HE for clinical use and overt HE to patients with grade II to IV.…”
mentioning
confidence: 99%